Characterization of Nanosized Carbide Precipitates in Multiple Microalloyed Press Hardening Steels - Hardy Mohrbacher; Linda Bacchi; Gloria Ischia; Stefano Gialanella; Michele Tedesco; Fabio D'Aiuto; Renzo Valentini (Metals, 2023)
Press hardening steel standardly relies on titanium microalloying for protecting boron from being tied up by residual nitrogen. This practice safeguards the hardenability effect of boron during die quenching. More recently, additional microalloying elements were added to press hardening steel to further improve properties and service performance. Niobium was found to induce microstructural refinement, leading to better toughness, bendability, and hydrogen embrittlement resistance. In that respect, niobium also extends the operating window of the press hardening process. Vanadium microalloying has been proposed to provide hydrogen trapping by its carbide precipitates. A recently developed press hardening steel employs all three microalloying elements in an attempt to further enhance performance. The current study analyses the microstructure of such multiple microalloyed press hardening steel, and compares it to the standard grade. Particularly, the effect of various heat treatments is investigated, indicating that the multiple microalloyed steel is more resistant against grain coarsening. TEM analysis is used to identify the various particle species formed in the steels, to track their formation, and to determine their size distributions. Nanosized microalloy carbide particles typically comprise a mixed composition involving niobium, titanium, and vanadium. Furthermore, these precipitates are incoherent to the matrix. Regarding tensile properties, it is found that the multiple microalloyed press hardening steel is superior to the standard grade.